Bleeding diathesis and gastro-duodenal ulcers in inherited cytosolic phospholipase-A2 alpha deficiency - Faioni, E M; Razzari, C; Zulueta, A; Femia, E A; Fenu, L; Trinchera, M; Podda, G M; Pugliano, M; Marongiu, F; Cattaneo, M (Thrombosis and haemostasis, 2014)
Arachidonic acid (AA), when cleaved from phospholipids by cytosolic phospholipase A2 alpha (cPLA2a), generates eicosanoids, with pro-hemostatic, pro-inflammatory, vasoactive and gastro-protective functions. We describe a patient (27-year-old man) and his twin-sister with early-onset bleeding diathesis and recurrent gastro-intestinal (GI) ulcers. Platelet aggregation/δ-granules secretion by collagen was impaired, but normal by AA; serum levels of thromboxane (Tx) B2 and 12-hydroxyeicosatetraenoic acid, and urinary levels of 11-dehydro-TxB2 were extremely low. Patients were homozygous for 1723G>C transition in PLA2G4A gene, which changed the codon for Asp575 to His. GI ulcers affected 5/14 heterozygous (< 40 years) and 1/16 wild-type homozygous (> 60 years) family members; none had bleeding diathesis. The proband, his sister and mother also had mildly reduced factor XI levels. Platelet messenger RNA expression did not differ among subjects with different PLA2G4A genotypes. Conversely, platelet cPLA2a was undetectable by Western Blotting in the proband and his sister, and decreased in 1723G>C heterozygous subjects, suggesting that the variant is transcribed, but not translated or translated into an unstable protein. We described a syndromic form of deficiency of cPLA2a , characterised by recurrent GI ulcers and bleeding diathesis, associated with mild inherited deficiency of factor XI. Unlike other reported patients with cPLA2a deficiency, these patients had extremely low levels of platelet TxA2 biosynthesis.